2000
DOI: 10.1046/j.1523-1755.2000.01001.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic profiles of cultured glomerular cells following repeated cycles of hydrocarbon injury

Abstract: These observations suggest that hydrocarbon injury induces differential responses in cells of the glomerulus, resulting in inhibition of GMCs and selective growth advantage of GVECs. These alterations are reminiscent of critical events described in the pathogenesis of focal segmental glomerulosclerosis and raise important questions about the pathogenesis of hydrocarbon-induced nephropathies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Our results are in line with these previous publications and show the relative high oxidative stress and DNA damage in liver and lung. Numerous studies have indicated that renal changes are induced by B[a]P treatment in rodents ( Alejandro et al., 2000 ; Knuckles et al., 2001 ; Nanez et al., 2005 ). As a result, the findings showed oxidative stress and DNA damages in kidney induced by B[a]P. The stomach is also exposed to exogenous carcinogens such as B[a]P which is used to induce tumors in the lung, skin, and forestomach of mice ( Lee et al., 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in line with these previous publications and show the relative high oxidative stress and DNA damage in liver and lung. Numerous studies have indicated that renal changes are induced by B[a]P treatment in rodents ( Alejandro et al., 2000 ; Knuckles et al., 2001 ; Nanez et al., 2005 ). As a result, the findings showed oxidative stress and DNA damages in kidney induced by B[a]P. The stomach is also exposed to exogenous carcinogens such as B[a]P which is used to induce tumors in the lung, skin, and forestomach of mice ( Lee et al., 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Renal toxicity in rodents is often induced by B(a)P treatment (Alejandro et al , 2000). Subchronic oral BaP dosing increased cast formation in Sprague Dawley rats (Knuckles et al , 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This may be related to the more lipophilic substitution (O-methyl group) at the C-3’ position in the isorhamnetin molecule. Isorhamnetin, aflavonol aglycone, was investigated for its cytotoxicity and its influence on human hepatocellular carcinoma cells (BEL-7402) (Bao-song, 2006). The present study was designed to show the efficacy of PL against the toxic effects of B(a)P in an in vivo experimental model.…”
Section: Introductionmentioning
confidence: 99%
“…Subchronic oral dosing of male rats with BaP induces renal cast formation (29). Repeated challenge of glomerular cells in culture with BaP and related aromatic hydrocarbons induce phenotypic changes (2) and altered mitogenic signaling (44). If these alterations occur in vivo, progressive loss of renal glomerular function would be expected.…”
mentioning
confidence: 99%